Stent Graft in the Treatment of Pseudoaneurysms of the Hepatic Arteries. (October 2013) - Lü, Peng-Hua; Zhang, Xi-Cheng; Wang, Li-Fu; Chen, Zhao-Lei; Shi, Hai-Bin
Objective: The purpose of our study was to evaluate the technical feasibility, procedural complications, clinical follow-up, and computed tomography (CT) scan outcomes of hepatic artery pseudoaneurysms (HAPs) treated with stent graft. Methods: Between October 2004 and October 2009, we treated 8 patients with HAPs with stent graft. Results: Stent graft deployment was technically successful in all the patients. Complete exclusion of the pseudoaneurysm preserving patency of the hepatic artery was achieved in 6 patients. Total occlusion of the common hepatic artery was observed in 1 patient, and vasospasm of proper hepatic artery and endoleak from distal stent margin were observed in another patient. The 2 patient were controlled through occlusion parent artery with coils. After these procedures, symptoms of bleeding and abdominal pain disappeared. Follow-up enhanced CT scan was performed at an average of 14 months (range, 6-26months), which showed complete disappearance of the HAP and patency of the stent without intrastent stenosis in 6 patients who had successful deployment of the stent. Conclusions: Endovascular treatment of HAPs using stent graft can maintain the hepatic artery blood flow and could be considered as an alternative to embolization.